EFFECTIVENESS OF ACUPRESSURE ON REDUCTION OF PREMENSTRUAL SYNDROME (PMS) AMONG ADOLESCENT GIRLS (16-18YRS) (International Journal of Food and Nutritional Sciences, 2022)
A quasi experimental pretest and post test with control group design was adopted to assess the effectiveness of acupressure on reduction of premenstrual syndrome among adolescent girls (16-18yrs) in selected schools at Chennai, Tamil nadu. Quantitative approach was used to collect data.